2022
DOI: 10.1017/etds.2022.5
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimension of escaping sets of meromorphic functions II

Abstract: A function which is transcendental and meromorphic in the plane has at least two singular values. On the one hand, if a meromorphic function has exactly two singular values, it is known that the Hausdorff dimension of the escaping set can only be either $2$ or $1/2$ . On the other hand, the Hausdorff dimension of escaping sets of Speiser functions can attain every number in $[0,2]$ (cf. [M. Aspenberg and W. Cui. Hausdorff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
2
0
2
Order By: Relevance
“…As a consequence of our main result, we also have the following theorem which completes the study begun in [2] and continued in [3].…”
Section: Introduction and Main Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…As a consequence of our main result, we also have the following theorem which completes the study begun in [2] and continued in [3].…”
Section: Introduction and Main Resultssupporting
confidence: 66%
“…Our results can be seen as a contribution to recent efforts to understand the differences and similarities between the classes B and S. We refer to [2,3,10,15,16,17,21] and the survey [37] for results in this direction. As an example we mention the recent result of Albrecht and Bishop [1] who showed that given δ > 0 there exists an entire function f ∈ S such that 1 < dim J(f ) < 1 + δ.…”
Section: Introduction and Main Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…若 R(f ) 分别为空、有限或无限集, 则称 f 分别为不可重整、(至多) 有限可重整或无穷可重整. 对于可重整的单临界多项式, 根据重整的 组合可将其划分成 primitive 和 satellite 等类型 17) (参见文献 [499, 第 7.3 小节]).…”
Section: Fatou-juliaunclassified
“…再结 合 J(tan z) = R 和 Misiurewicz 的结果 J(e z ) = C [525] 可知, 有界型超越亚纯函数 Julia 集的 Hausdorff 维数可以取到区间 (0, 2] 中的任何值. Bergweiler 和崔巍巍 [80] 证明了对于任意 s ∈ (0, 2], 存在一个有 限型的超越亚纯函数 f (事实上仅有 3 个奇异值), 使得 dim H J(f ) = s. 对于有限型超越亚纯函数逃 逸集的 Hausdorff 维数研究可参见文献 [16,17].…”
Section: 超越unclassified